ok i'm trying to do 2 proofs for gcd show that if ax + by =1 then gcd(a,b)=1 and gcd(a,a+k) divides k just need a little hint on where to start thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by action259 ok i'm trying to do 2 proofs for gcd show that if ax + by =1 then gcd(a,b)=1 Suppose c>1 is the gcd(a,b), then c divides (ax+by), but c does not divide 1, a contradiction. and gcd(a,a+k) divides k let c be the gcd(a, a+k), then by definition c divides a, and c divides a+k. RonL
View Tag Cloud